Fostering Children's Expressive Language through the Enchanting Journey of Storytelling Roll Books - Farista, Dian; Priyanti, Nita (Journal of Islamic Education Students (JIES), 2023)
This study aims to explore the crucial role of language proficiency in everyday life, particularly among children in Group B at TK 'Aisyiyah Bustanul Athfal 72. A descriptive qualitative design approach was employed, with data collected through observation, interviews, and documentary studies. The research findings indicate that children in this group possess significant expressive language abilities. They can engage in two-way communication with peers and adults, narrate the content of stories read to them, and express desires or disagreements verbally. Importantly, the optimal involvement of parents and the home environment contributes positively to providing stimulation to enrich the vocabulary of children through activities that reinforce the content of storytelling introduced at school. The results of this research can serve as a foundation for better understanding and enhancing language learning for children at the preschool level.